Internationalization barriers of SMEs from developing countries: a review and research agenda. Issue 6 (4th July 2020) - Chandra, Ashna; Paul, Justin; Chavan, Meena
Abstract : Purpose: This paper reviews the literature on internationalization barriers of small and medium enterprises (SMEs) from developing countries. The purposes of the study are: (1) to explicitly point out specific factors influencing the growth and internationalization of SMEs from developing countries and (2) to identify the research gaps to provide lucid and succinct directions for future research in this area. Design/methodology/approach: The authors selected relevant papers from journals listed on Web of Science and Scopus databases. Findings: It was found that there are large number of questions remain unanswered regarding the internationalization of SMEs from developing countries regarding the factors determining their growth and internationalization. Originality/value: This review distinctively accentuates previous studies on such barriers influencing the growth of SMEs from developing countries and systematically synthesize the issues faced by those SMEs. Thus, the authors seek to provide a comprehensible platform for researchers working in this area.